PAX2+ Mesenchymal Origin of Gonadal Supporting Cells Is Conserved in Birds - Estermann, Martin A.; Mariette, Mylene M.; Moreau, Julie L. M.; Combes, Alexander N.; Smith, Craig A. (Frontiers in Cell and Developmental Biology, 2021)
During embryonic gonadal development, the supporting cell lineage is the first cell type to differentiate, giving rise to Sertoli cells in the testis and pre-granulosa cells in the ovary. These cells are thought to direct other gonadal cell lineages down the testis or ovarian pathways, including the germline. Recent research has shown that, in contrast to mouse, chicken gonadal supporting cells derive from a PAX2/OSR1/DMRT1/WNT4 positive mesenchymal cell population. These cells colonize the undifferentiated genital ridge during early gonadogenesis, around the time that germ cells migrate into the gonad. During the process of somatic gonadal sex differentiation, PAX2 expression is down-regulated in embryonic chicken gonads just prior to up-regulation of testis- and ovary-specific markers and prior to germ cell differentiation. Most research on avian gonadal development has focused on the chicken model, and related species from the Galloanserae clade. There is a lack of knowledge on gonadal sex differentiation in other avian lineages. Comparative analysis in birds is required to fully understand the mechanisms of avian sex determination and gonadal differentiation. Here we report the first comparative molecular characterization of gonadal supporting cell differentiation in birds from each of the three main clades, Galloanserae (chicken and quail), Neoaves (zebra finch) and Palaeognathe (emu). Our analysis reveals conservation of PAX2+ expression and a mesenchymal origin of supporting cells in each clade. Moreover, down-regulation of PAX2 expression precisely defines the onset of gonadal sex differentiation in each species. Altogether, these results indicate that gonadal morphogenesis is conserved among the major bird clades.